Peran Roh Kudus dalam Penginjilan Virtual di Era Digital - Ananius, Bambang Setiadi (STTI Harvest Semarang, 2024)
This research discusses the role of the Holy Spirit in the ministry of preaching the gospel in the digital era, especially through virtual platforms. Today's churches are required to adapt to the development of information technology, especially in delivering the Gospel message to people known as digital society. This research uses the library method with a descriptive qualitative approach. Research data was obtained by analyzing relevant Bible verses, and online literature. From this research, it was found that evangelism through social media cannot be separated from the participation and role of the Holy Spirit who enables every believer to preach the gospel effectively in the virtual world. The Holy Spirit acts to bring people to repentance, to convict people of sin, of the truth of the gospel of Christ and the judgment of God and to give gifts to virtual evangelists in carrying out the task of evangelism on various social media platforms. Without the role of the Holy Spirit, the virtual preaching of the gospel will not achieve its purpose. It can be concluded that the Holy Spirit plays a vital role in virtual evangelism to fulfill the divine mission in cyberspace. Suggestions for further research include the need to develop a “digital pneumatology” that recognizes and articulates the work of the Holy Spirit in and through digital technology. AbstrakPenelitian ini membahas peran Roh Kudus dalam pelayanan pemberitaan Injil di era digital, khususnya melalui platform virtual. Gereja-gereja saat ini dituntut untuk beradaptasi dengan perkembangan teknologi informasi, terutama dalam menyampaikan pesan Injil kepada masyarakat yang dikenal sebagai masyarakat digital. Penelitian ini menggunakan metode pustaka dengan pendekatan kualitatif deskriptif. Pengumpulan data dilakukan dengan menganalisis ayat-ayat Alkitab dan literatur teologi secara luring dan on-line yang terkait topik penelitian. Dari penelitian ini, ditemukan bahwa penginjilan melalui media sosial tidak dapat terlepas dari penyertaan dan peran Roh Kudus yang memampukan setiap orang percaya untuk memberitakan Injil dengan efektif di dunia virtual. Roh Kudus bertindak membawa orang-orang pada pertobatan, menginsyafkan manusia akan dosa, akan kebenaran Injil Kristus dan penghakiman Allah serta memberikan karunia kepada para penginjil virtual dalam melaksanakan tugas penginjilan di berbagai paltform media sosial. Tanpa peran Roh Kudus, pemberitaan Injil yang dilakukan secara virtual, tidak akan mencapai tujuannya. Dapat disimpulkan bahwa Roh Kudus memainkan peran vital dalam penginjilan virtual guna menggenapi misi Ilahi di dunia maya.